Increase of operating reliability of the travel wheel using the use of the elastic inserts - Fidrovska, Nataliia; Slepuzhnikov, Evgen; Larin, Oleksiy; Varchenko, Ivan; Lipovyi, Voloymyr; Afanasenko, Kostiantyn; Harbuz, Serhii (Scientific Route OÜ, Estonia, 2020)
The aim of research is to substantiate the rational design of the travel wheel based on the determination of the dynamic forces arising from the movement of the freight carriage and the crane bridge. The research methodology is based on analytical methods for studying dynamic forces in the mechanism of movement of the cargo carriage of an overhead crane. The obtained solution of the three-mass dynamic scheme of the movement of the freight carriage. To verify the theoretical data obtained, an experiment was carried out on an overhead crane with a lifting capacity of 5, span of 22.5 m, lifting height of 8 m, operating mode of 7 K. The study of the vibration state was carried out on the crane beam in the middle of the span, on the axis of the driven wheel of the crane trolley with an elastic insert and on the axis of the drive wheel of the crane trolley of a conventional design. Crane wheels are the fastest wearing parts of a crane. A decrease in their durability leads to an increase in repair costs and crane downtime. Therefore, increasing the durability of crane travel wheels is an urgent task of modern crane construction. All designs of travel wheels are quite rigid and do not perceive shocks and distortions arising from the deviation of the rail track from the recommended values and lead to significant wear of the flanges and rails. The analysis of the obtained solutions showed that when using a travel wheel with an elastic insert, the dynamic factors during the movement of the freight carriage decrease. Dependences are obtained for determining the dynamic forces arising from the movement of the travel crane wheel, taking into account the rigidity of the elastic ring, which is installed in the travel wheel. The analysis of the regularities of the formation of vibration signs at different points of the overhead crane structure is carried out. The proposed design and calculation method for a travel wheel with an elastic insert improves its operational reliability.
Keywords: travel wheel; elastic insert; bridge crane; cargo trolley; dynamic loads of vibration acceleration